Specific in vitro cleavage of a Leishmania virus capsid-RNA-dependent RNA polymerase polyprotein by a host cysteine-like protease. - Ro, Y T (1997)
Antibodies raised against baculovirus-expressed RNA-dependent RNA polymerase (RDRP) recognized a 95-kDa antigen and two smaller proteins in sucrose-purified Leishmania virus particles isolated from infected parasites. The 95-kDa antigen is similar in size to one predicted by translation of the RDRP open reading frame (ORF) alone. In an effort to reconcile in vitro observations of translational frameshifting on Leishmania RNA virus 1-4 transcripts, we have developed an in vitro cleavage assay system to explore the possibility that the fusion polyprotein is proteolytically processed. We show that coincubation a synthetic Cap-Pol fusion protein with lysates from Leishmania parasites yields major cleavage products similar in size to those encoded by the individual capsid and RDRP genes as well as the antigens detected in vivo. The major 82- and 95-kDa major cleavage products are specifically immunoprecipitated by capsid- or polymerase-specific antibodies, respectively, showing that cleavage occurs at or near the junction of the two functional domains. Protease inhibitor studies suggest that a cysteine-like protease is responsible for cleavage in the in vitro assay system developed here. From these results, we suggest that failure to detect a capsid-polymerase fusion protein produced by translational frameshifting in vivo may be due to specific proteolytic processing.